Analysis and Strengthening of the Regulation of Digital Assets as Objects of Inheritance in Indonesian Inheritance Law - Hardiyanto Putra Limonu (SEAN Institute, 2026)
The development of digital assets in Indonesia has shown significant growth, both in terms of the number of users and their economic value. Digital assets such as cryptocurrencies, NFTs, and digital accounts have become part of society's wealth and have the potential to become objects of inheritance. However, the Indonesian inheritance law system does not yet have explicit regulations regarding the status and inheritance mechanisms of digital assets, thus creating legal uncertainty and potentially hampering the protection of heirs' rights. This study aims to analyze the construction of regulations for digital assets as objects of inheritance in Indonesian inheritance law and examine the legal consequences of this lack of regulation on legal certainty and the protection of heirs' rights. The method used is normative legal research with a statutory, conceptual, and interdisciplinary approach through a literature review of primary, secondary, and tertiary legal materials analyzed qualitatively using systematic and grammatical interpretation methods. The results show that digital assets conceptually fulfill the elements of an inheritance object because they have economic value, can be owned, and can be transferred. However, Indonesian positive law does not yet provide clear regulations regarding the inheritance mechanism. This legal vacuum has resulted in legal uncertainty, potential disputes between heirs, difficulties in accessing digital assets, and weak legal protection for heirs. This study concludes that adaptive and comprehensive legal reforms are needed to accommodate the characteristics of digital assets within the Indonesian inheritance law system. These findings are expected to contribute to the development of contemporary inheritance law and serve as an academic basis for formulating legal policies related to the inheritance of digital assets in Indonesia.